2017
DOI: 10.5897/ajar2017.12634
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the levels of cassava commercialization among smallholder farmers in Kenya: A multinomial regression approach

Abstract: Cassava commercialization is a concept that has been used by many development practitioners because of its possible strategic role in transforming livelihoods of smallholder farmers in subSaharan Africa, including Siaya and Kilifi Counties in Kenya. This concept can easily be implemented when the levels of commercialization is known. However, empirical evidence reveals little information on the levels of cassava commercialization amongst smallholder farmers in these counties. Thus effective policy intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(22 reference statements)
3
5
0
Order By: Relevance
“…Hence, as the household size increases, smallholder cassava farmers are more likely to participate in lower categories of commercialization levels. This result is similar to that of Florence et al (2017) who found out that, in Kilifi county households with larger number of people were likely to participate at lower categories of commercialization level because larger households exerted pressure on the limited resources available in the homestead including farm produce. Similarly, Agwu et al (2013) found out that, an increase in the household size reduces the probability of farmers' orientation towards market commercialization due to its effect on increased domestic consumption needs.…”
Section: Ordered Probit Model Results For Factors That Influence the Level Of Commercialization Among Smallholder Cassava Farmerssupporting
confidence: 88%
See 4 more Smart Citations
“…Hence, as the household size increases, smallholder cassava farmers are more likely to participate in lower categories of commercialization levels. This result is similar to that of Florence et al (2017) who found out that, in Kilifi county households with larger number of people were likely to participate at lower categories of commercialization level because larger households exerted pressure on the limited resources available in the homestead including farm produce. Similarly, Agwu et al (2013) found out that, an increase in the household size reduces the probability of farmers' orientation towards market commercialization due to its effect on increased domestic consumption needs.…”
Section: Ordered Probit Model Results For Factors That Influence the Level Of Commercialization Among Smallholder Cassava Farmerssupporting
confidence: 88%
“…This is because, an increase in distance to the market increases transport and production costs and therefore reducing gains from cassava farming hence discoursing cassava marketing. This result corresponds with that of Florence et al (2017), Muhammad-Lawal et al (2014, Agwu et al (2013) and Martey et al (2012) who found a negative relationship between distance to the market and commercialization, whereby Florence et al (2017) concluded that it was due to increase in transport and transaction costs.…”
Section: Ordered Probit Model Results For Factors That Influence the Level Of Commercialization Among Smallholder Cassava Farmerssupporting
confidence: 82%
See 3 more Smart Citations